1979
DOI: 10.1016/0013-4694(79)90254-2
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-like neuronal sources of theta rhythm in dorsal hippocampus, dendate gyrus and cingulate cortex of the urethane-anesthetized rat

Abstract: Spatial distribution of theta activity was investigated in the dorsal hippocampal formation and overlying neocortex of the urethane-anesthetized rat. Laminar phase profiles from semi-microelectrode penetartions showed approximately 180 degrees phase shifts combined with small amplitude values in stratum radiatum of CA1, instratum moleculare of the dentate gyrus and in layer V/VI of the cingulate cortex at theta peak frequency. Evidence has been presented that layers of neurons in CA1, in the dorsal granular la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 15 publications
5
26
0
Order By: Relevance
“…While urethane has been used for studies of activity in limbic cortical structures, including cingulate cortex (Feenstra and Holsheimer, 1979), urethane has been described as anticonvulsant in somatosensory cortex (Heltovics et al, 1995) and this may result from a suppression of glutamate release (Moroni et al, 1981). Such a mechanism appears to be specific to some synapses in neocortex and possibly hippocampal formation.…”
Section: Urethane Permits Seizures Without Motor Convulsionsmentioning
confidence: 97%
“…While urethane has been used for studies of activity in limbic cortical structures, including cingulate cortex (Feenstra and Holsheimer, 1979), urethane has been described as anticonvulsant in somatosensory cortex (Heltovics et al, 1995) and this may result from a suppression of glutamate release (Moroni et al, 1981). Such a mechanism appears to be specific to some synapses in neocortex and possibly hippocampal formation.…”
Section: Urethane Permits Seizures Without Motor Convulsionsmentioning
confidence: 97%
“…Inactivation or lesion of the medial septum abolishes the theta rhythm, giving rise to the initial concept that the medial septum is the pacemaker of the hippocampal theta activity (Stewart and Fox, 1990). However, independent theta rhythmicity has now been proposed for the majority of processing nodes in which it has been investigated including thalamic and deeper nuclei (McNaughton et al, 1995; Kirk et al, 1996; Woodnorth et al, 2003), colliculus (Pedemonte et al, 1996), rhinal cortex (Bilkey and Heinemann, 1999; Collins et al, 1999; Mizuseki et al, 2009), amygdala (Seidenbecher et al, 2003; Popescu et al, 2009; Rutishauser et al, 2010), cingulate cortex (Feenstra and Holsheimer, 1979; Borst et al, 1987; Talk et al, 2004; Hyman et al, 2005; Tsujimoto et al, 2006, 2010; Young and McNaughton, 2009; Womelsdorf et al, 2010), dorsal striatum, nucleus accumbens, and ventral tegmental area (Tabuchi et al, 2000; Kocsis et al, 2001; DeCoteau et al, 2007a,b; Lansink et al, 2009), and is found in all four lobes in the neocortex (see also below) (Cantero et al, 2003; Sirota et al, 2008). …”
Section: Theta Rhythmic States At Single Neuron Membranes and Large Smentioning
confidence: 99%
“…1), having an amplitude maximum at about the fissure, a gradual phase reversal in stratum radiatum and a second, sudden phase reversal in the molecular layer or just underneath the granular layer of the upper blade of the dentate gyrus in the urethane-anesthetized rat 7,15. Besides this, we observed another phase reversal in the lower blade of the dentate gyrus.…”
Section: Introductionmentioning
confidence: 99%